ANALISIS MANFAAT RASIO KEUANGAN DALAM MEMPREDIKSI FINANCIAL DISTRESS PADA PERBANKAN (2007-2012) - Rizky Indriyani Siregar; Syarief Fauzie (Departemen Ekonomi Pembangunan USU, 2014)
This research has a purpose to provide financial ratios in predicting financial distress of bank. The financial ratios that are used are CAR, ROA, ROE, LDR, BOPO, NIM and NPL. By using purposive sampling method, there 11 banks which experience financial distress and 11 banks which do not experience financial distress as comparison. This research used Logistic Regression to analyze financial ratios in predicting financial distress. Logistic Regression was used twice by using data of 2 years prior to financial distress and 1 year prior to financial distress. The result showed that logistic regression model by using data of 2 years prior to financial distress was a good model while model by using data of 1 year prior to financial ratios was not a good model and could not be used. The final result showed that CAR, NIM, and NPL have positive influence while ROA, ROE, LDR and BOPO have negative influence in predicting financial distress of bank.Keyword: financial distress, financial ratios, logistic regression